Is seeking health information online different from seeking general information online?. (April 2015) - Kim, Yong-Mi
Increasing use of the Internet for health information delivery has created considerable discussion among digital divide scholars (i.e. how online information delivery benefits those individuals in higher socioeconomic brackets more than their counterparts). Because it is health information, we need to integrate how patients seek out online information. This study included patients' information-seeking behaviour along with digital divide scholars' constructs (i.e. literacy and computer skills). Using 1617 observations from the 2010 Pew Internet and American Life Project, this study found that individuals with a significant number of health problems, who are likely to be in a lower income bracket, are proactive online health information seekers; however, they are less likely to search general information. This finding adds value to existing research revealing that usefulness, which has been overlooked in online health information seeking, is important and should be a part of the research model.